Microglial Activation Modulated by P2X4R in Ischemia and Repercussions in Alzheimer’s Disease - Castillo, Carolina; Saez-Orellana, Francisco; Godoy, Pamela Andrea; Fuentealba, Jorge (Frontiers in Physiology, 2022)
There are over 80 million people currently living who have had a stroke. The ischemic injury in the brain starts a cascade of events that lead to neuronal death, inducing neurodegeneration which could lead to Alzheimer’s disease (AD). Cerebrovascular diseases have been suggested to contribute to AD neuropathological changes, including brain atrophy and accumulation of abnormal proteins such as amyloid beta (Aβ). In patients older than 60 years, the incidence of dementia a year after stroke was significantly increased. Nevertheless, the molecular links between stroke and dementia are not clearly understood but could be related to neuroinflammation. Considering that activated microglia has a central role, there are brain-resident innate immune cells and are about 10–15% of glial cells in the adult brain. Their phagocytic activity is essential for synaptic homeostasis in different areas, such as the hippocampus. These cells polarize into phenotypes or subtypes: the pro-inflammatory M1 phenotype, or the immunosuppressive M2 phenotype. Phenotype M1 is induced by classical activation, where microglia secrete a high level of pro- inflammatory factors which can cause damage to the surrounding neuronal cells. Otherwise, M2 phenotype is the major effector cell with the potential to counteract pro-inflammatory reactions and promote repair genes expression. Moreover, after the classical activation, an anti-inflammatory and a repair phase are initiated to achieve tissue homeostasis. Recently it has been described the concepts of homeostatic and reactive microglia and they had been related to major AD risk, linking to a multifunctional microglial response to Aβ plaques and pathophysiology markers related, such as intracellular increased calcium. The upregulation and increased activity of purinergic receptors activated by ADP/ATP, specially P2X4R, which has a high permeability to calcium and is mainly expressed in microglial cells, is observed in diseases related to neuroinflammation, such as neuropathic pain and stroke. Thus, P2X4R is associated with microglial activation. P2X4R activation drives microglia motility via the phosphatidylinositol-3-kinase (PI3K)/Akt pathway. Also, these receptors are involved in inflammatory-mediated prostaglandin E2 (PGE2) production and induce a secretion and increase the expression of BDNF and TNF-α which could be a link between pathologies related to aging and neuroinflammation.